Comparison and analysis of drilling gas flow based on continuous and dual media - Hao Yongjiang; Hu Jie (Scientific Reports)
Abstract The mathematical models of drilling gas flow based on the continuous medium and pore-fracture dual media were established according to the law of mass conservation, aiming to derive a gas flow model in coal that better reflects field conditions. The physical model was then simplified, the computational grid and nodes were defined, and the finite difference method was employed for model discretization. Subsequently, VB programming was used to perform numerical calculations. The variation characteristics of the drilling gas emission rate and cumulative flow were obtained. Meanwhile, drilling gas flow was measured by connecting an orifice flowmeter and a high-precision gas meter in series to enhance measurement accuracy. The measured results were compared with the simulation results derived from both the continuous and dual media models. The findings indicate that the simulation results for both gas emission rate and cumulative flow based on the dual media model are more consistent with the measured data, whereas the continuous-medium exhibit significant deviations. Therefore, the dual media-based model demonstrates better agreement with the actual drilling gas flow process.